Court processing and sentencing of drinking drivers: Using new methodologies - Nienstedt, Barbara Cable (Journal of quantitative criminology, 1988)
Driving while intoxicated (DWI) offenses provide a unique focal point for research in criminology. In recent years, legislative and media attention has increasingly focused on the harmful acts of drunk drivers, but little is known of the characteristics of individuals arrested for driving while drunk or of the court processing and sanctioning of such offenders. The research presented here uses a variety of methodological techniques to analyze individual-level court processing data for persons convicted of DWI on a revoked license. We find that the population of persons processed for this offense have certain characteristics which are not unlike those of persons processed for street crimes. Further, we find evidence of differential sanctioning related to ethnicity and level of education. We conclude with a call for future investigation of court processing to understand better why the DWI legislative mandate is being applied differently across social groups.